2012
DOI: 10.3857/roj.2012.30.3.108
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative radiotherapy for endometrial cancer

Abstract: PurposeTo investigate the prognostic factors and effectiveness of postoperative radiotherapy alone for endometrial carcinoma.Materials and MethodsSixty four patients with stage I-III endometrial cancer (EC) treated with postoperative radiotherapy alone between January 1989 and December 2008 at the Keimyung University Dongsan Medical Center were chosen for the present study. Typically, total hysterectomy, salpingo-oophorectomy and lymphadenectomy were performed on the patient's pelvis. Total dose from 50.4 Gy t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…One hundred nine patients were treated with concurrent CTRT (86.5%), 10 patients with CT followed by RT (7.9%), and 7 patients with RT followed by CT (5.6%). Adjuvant CT was delivered with a median of 6 cycles (range, [3][4][5][6][7][8][9][10][11][12], although 3 patients received only 2 cycles. Six patients did not complete the full course of CT because of G4 hematologic toxicity (n = 2), intravascular hemolysis (n = 1), or no available data on toxicity (n = 3).…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…One hundred nine patients were treated with concurrent CTRT (86.5%), 10 patients with CT followed by RT (7.9%), and 7 patients with RT followed by CT (5.6%). Adjuvant CT was delivered with a median of 6 cycles (range, [3][4][5][6][7][8][9][10][11][12], although 3 patients received only 2 cycles. Six patients did not complete the full course of CT because of G4 hematologic toxicity (n = 2), intravascular hemolysis (n = 1), or no available data on toxicity (n = 3).…”
Section: Treatmentmentioning
confidence: 99%
“…Traditionally, postoperative radiotherapy (RT) has been employed in stage IIIC endometrial carcinoma to improve locoregional control and outcome [1][2][3]. Recently, with advances in chemotherapy (CT), the majority of adjuvant treatment consists of CT with or without RT in high-risk or advanced stage endometrial cancer; in randomized settings, some investigators are trying CT intensification instead of RT [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal adjuvant management for patients with advanced endometrial cancer has yet to be defined, particularly for IIIA patients as incidence is low, representing only 2.6% of patients with endometrial cancer [ 7 ]. Radiotherapy (RT) has traditionally been employed in advanced endometrial carcinoma to improve locoregional control [ 8 , 9 ]. Several studies have evaluated the role of combined modality adjuvant therapy compared with a single modality in advanced endometrial cancer and have suggested that combined chemoradiotherapy (CTRT) can provide additional benefits compared with computed tomography (CT) or RT alone [ 10 - 13 ].…”
Section: Introductionmentioning
confidence: 99%